Assessing the social cost of housing projects on the built environment: Analysis and monetization of the adverse impacts incurred on the neighbouring communities - Celik, Tolga; Arayici, Yusuf; Budayan, Cenk (ELSEVIER SCIENCE INC, 2019)
Construction projects generate serious environmental adverse impacts on the adjacent residents. All those harmful consequences and damages that third parties or the community sustain due to the implementation of construction processes are called social costs. Although, the presence of social costs is widely mentioned in the literature, in the projects' initial cost estimation practices, the social costs are not estimated and included. Whereas since these costs are not compensated, problems can be emerged by the community. It is a truism that the majority of the models proposed to quantify the social costs have been concentrated on construction, repair, and maintenance of the infrastructure projects namely; utilities, roads, and highways. On the other hand, up to the present, a limited number of attempts has been made to quantify residential housing construction associated social costs. Thus, this research aims to expand and/or contribute to the existing body of knowledge via estimating how much social cost society surrounding residential housing construction sites are subjected to. For this purpose, a social cost estimation model is developed to assist industry professionals on how to estimate social costs in residential construction projects. The social cost estimation model is developed to provide guidance for phase by phase monetization of the residential construction associated social costs. In this paper, the model proposed for social cost estimation is validated via a case study in Turkey.
Keywords: Social cost; Social cost definition; Social cost quantification; Construction adverse impacts; Housing projects; Built environment; Neighbouring community; Environmental Sciences & Ecology